2014
DOI: 10.1097/pcc.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Nonrespiratory Pediatric Logistic Organ Dysfunction-2 Score Is a Good Predictor of Mortality in Children With Acute Respiratory Failure

Abstract: Our study demonstrates that the nonrespiratory Pediatric Logistic Organ Dysfunction-2 score of the entire PICU stay is highly predictive of death in children with acute respiratory failure of whom 94.3% were invasively ventilated. The nonrespiratory Pediatric Logistic Organ Dysfunction-2 score could represent the nonrespiratory organ failure definition tool whose development was recommended in the international expert recommendations on pediatric acute respiratory distress syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…A daily vasoactive inotrope score (VIS) was calculated to describe the need for vasoactive support [16]. The non-respiratory Pediatric Logistic Organ Dysfunction (PELOD) 2 score was calculated daily to describe organ dysfunction [17]. The use of neuromuscular blocking agents (NMBAs) was noted as well as total daily cumulative dosage of sedatives and analgesic drugs.…”
Section: Methodsmentioning
confidence: 99%
“…A daily vasoactive inotrope score (VIS) was calculated to describe the need for vasoactive support [16]. The non-respiratory Pediatric Logistic Organ Dysfunction (PELOD) 2 score was calculated daily to describe organ dysfunction [17]. The use of neuromuscular blocking agents (NMBAs) was noted as well as total daily cumulative dosage of sedatives and analgesic drugs.…”
Section: Methodsmentioning
confidence: 99%
“…We focused on acute respiratory failure because this diagnostic category constitutes a significant proportion of children admitted to the PICU, and these patients likely have a higher risk profile than many other populations of patients who require TI and MV. Furthermore, an overwhelming majority of children with acute respiratory failure require TI and MV [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…(27, 3133) Furthermore, hemodynamic instability is a predictor of mortality in pediatric patients with acute respiratory failure receiving mechanical ventilation. (2) Whether hemodynamic optimization before/during airway management could lead to improved outcomes remains to be determined. We also found that hospital characteristics such as non-teaching and minor teaching hospitals were associated with decreased mortality in the multivariable model.…”
Section: Discussionmentioning
confidence: 99%
“…(17) Even though mortality varies substantially depending on the definitions used(1, 2), mortality may exceed 40% in severe cases. (3, 4) Although there are no published incidence estimates for all pediatric patients, ICD-9-data from a study performed in 2000 estimates the annual incidence at greater than 5,000 cases each year in the United States in children between 5 and 17 years.…”
Section: Introductionmentioning
confidence: 99%